2012
DOI: 10.1371/journal.pone.0047242
|View full text |Cite
|
Sign up to set email alerts
|

Protein Linewidth and Solvent Dynamics in Frozen Solution NMR

Abstract: Solid-state NMR of proteins in frozen aqueous solution is a potentially powerful technique in structural biology, especially if it is combined with dynamic nuclear polarization signal enhancement strategies. One concern regarding NMR studies of frozen solution protein samples at low temperatures is that they may have poor linewidths, thus preventing high-resolution studies. To learn more about how the solvent shell composition and temperature affects the protein linewidth, we recorded 1H, 2H, and 13C spectra o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 38 publications
2
63
0
3
Order By: Relevance
“…This aspect can result in severe line-broadening due to the overlapping peaks of the individual conformers which exhibit different chemical shifts (inhomogeneous line-broadening) (Linden et al 2011;Siemer et al 2012). Indeed, previous work has found a remarkable correlation between experimentally observed 13 Ca line-width and protein backbone fluctuations as predicted from molecular dynamics (MD) simulations (Koers et al 2014).…”
Section: Contentmentioning
confidence: 99%
“…This aspect can result in severe line-broadening due to the overlapping peaks of the individual conformers which exhibit different chemical shifts (inhomogeneous line-broadening) (Linden et al 2011;Siemer et al 2012). Indeed, previous work has found a remarkable correlation between experimentally observed 13 Ca line-width and protein backbone fluctuations as predicted from molecular dynamics (MD) simulations (Koers et al 2014).…”
Section: Contentmentioning
confidence: 99%
“…With the application of dynamic nuclear polarization (DNP), one could even gain further in the signal-tonoise ratio, up to a factor of 660. (Can et al 2015) Unfortunately, starting at the freezing temperature of the solvent water, one typically observes a significant broadening of the protein resonances (Linden et al 2011;Siemer et al 2012). This effect compromises most benefits of an increased signal strength.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism involved is the freezing out of motional processes between conformations with similar energy (HenzlerWildman and Kern 2007) which are then observed separately, leading to heterogeneous line broadening (Linden et al 2011). Above 200 K it has been observed that proteins retain a significant amount of liquid-like water around them which stays mobile long after the freezing of the bulk solvent in the sample (Siemer and McDermott 2008;Siemer et al 2010;Siemer et al 2012). The conservation of this mobile water layer might have an influence on the line-broadening behavior observed, in particular for the solvent-exposed residues.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, rapid interconversion between the different states results in sharper signal, centered at an average frequency. Several reports indicate that the reduction (or elimination) of static disorder is related to the presence of fluid solvent in the surrounding of the macromolecule [16][17][18][19]; the occurrence of sharper average signals could thus be ascribed either to solvent collision with the biomolecule, which promote a conformational variability, or to lower-hindrance from the fluid solvent on the intrinsic fluctuation of the macromolecule as compared to a frozen solvent.…”
Section: Introductionmentioning
confidence: 99%